The Effect of Organizational Commitment, Decentralization and Management Accounting Systems on Managerial Performance with Organizational Culture as a Moderating Variable - Seti Nugroho, Erwan; Hamidah Rustiana, Siti (Interdiciplinary Journal and Hummanity (INJURITY), 2023)
This study aims to determine the effect of organizational commitment, decentralization and management accounting systems on managerial performance with organizational culture as a moderating variable. This research method is included in quantitative research with primary data sources. Data analysis in this study used the WarpPLS Version 7.0 data processing tool. The results showed that Organizational Commitment, Decentralization and Management Accounting Systems had a positive and significant effect on Managerial Performance, Organizational Commitment and Management Accounting Systems had a positive and significant effect on Organizational Culture. Decentralization has no significant effect on Organizational Culture. Organizational Culture has a positive and significant effect on Managerial Performance. Organizational Culture does not moderate Organizational Commitment, Decentralization and Management Accounting Systems on Managerial Performance.